1993
DOI: 10.1007/bf00279913
|View full text |Cite
|
Sign up to set email alerts
|

Altered promoter binding of the TATA box-binding factor induced by the transcriptional activation domain of VP16 and suppressed by TF11A

Abstract: The acidic transcriptional activation domain of the Herpes simplex virus protein VP16 has been shown to bind directly to both the TATA box-binding factor TBP and the general initiation factor TFIIB. Using DNase I footprinting assays, we have shown here that the VP16 activation domain qualitatively alters binding of Saccharomyces cerevisiae TBP to a TATA sequence in DNA. The effect of VP16 on promoter binding by TBP was reduced by mutations in VP16 known to reduce transactivation and could not be overcome by in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…In addition, the VP16 activation domain inhibits partially the TBP-TATA interaction, which is mediated by the concave face of TBP. It should be noted that inhibition of the TBP-TATA interaction and͞or TBP-mediated transcription by some activators has been reported by several groups (9,33), but the possibility that this effect could be due to activator interactions with the concave face of TBP has not previously been recognized.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the VP16 activation domain inhibits partially the TBP-TATA interaction, which is mediated by the concave face of TBP. It should be noted that inhibition of the TBP-TATA interaction and͞or TBP-mediated transcription by some activators has been reported by several groups (9,33), but the possibility that this effect could be due to activator interactions with the concave face of TBP has not previously been recognized.…”
Section: Discussionmentioning
confidence: 99%
“…The potent transactivation domain of VP16 enhances transcription from the promoter by multiple ways- 1) by recruiting 38 and stabilizing 39 the transcriptional machinery on the promoter by interacting with different transcriptional co-activators like TBP, TFIID, TFIIA, TFIIH 4042 and with the Mediator (TRAP-SMCC-ARC) complex 43 2) by relieving nucleosome-mediated repression 44 and iii) by facilitating chromatin remodeling 45 . When the chimeric activator binds to Gal4-binding sites located upstream of the TATA box of a promoter they stimulate transcription in a synergistic fashion 45,46 .…”
Section: Discussionmentioning
confidence: 99%
“…In many other cases, binding of a protein to a single binding site causes bending of DNA (49 -51). DNaseI footprinting studies with these proteins, however, revealed only a small number of hypersensitive sites, generally located within the area protected against cleavage (2,(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62). DNaseI footprints of E. coli Lrp with several target promoter fragments show protection from DNaseI over a range of 100 bp or even longer, due to multiple binding sites.…”
Section: Fig 9 Sds-page Analysis Of Cross-linking Experiments Withmentioning
confidence: 99%